Assessing meteorological uncertainties in dispersion forecasts using a NWP Ensemble Prediction System. (8th February 2011) - Jones, Andrew R.
The use of ensembles of meteorological forecasts is explored in the context of dispersion modelling for emergency-response applications such as nuclear accidents or chemical releases. Specification of meteorology is often a major source of uncertainty in dispersion predictions. The ensemble methodology, routinely used in Numerical Weather Prediction (NWP), is followed in which multiple realisations of the dispersion are computed. The Met Office's Lagrangian particle model, NAME III, is applied to the ETEX 1 long-range tracer experiment using an ensemble forecast produced at the European Centre for Medium-Range Weather Forecasts. Some issues in ensemble dispersion prediction are discussed, illustrated by results from the case study.